Molecular analysis of HLA class II associations with hepatitis B virus clearance and vaccine nonresponsiveness. - Godkin, A; Davenport, M; Hill, A (2005)
Clearance of acute hepatitis B virus (HBV) infection is associated with a vigorous CD4+ T-cell response focusing on the core protein. HLA class II glycoproteins present viral peptides to CD4+ T cells and influence the immune responses. HLA-DRB1*1301/2 have been associated with viral clearance, and HLA-DRB1*0301 is associated with nonresponse to vaccination with envelope proteins. Binding affinities of overlapping peptides covering the core and envelope proteins of HBV were measured to HLA glycoproteins encoded by HLA-DRA1*0101,-DRB1*0101 (HLA-DR1), HLA-DRA1*0101,-DRB1*0301 (HLA-DR3), HLA-DRA1*0101,-DRB1*0701 (HLA-DR7) and HLA-DRA1*0101,-DRB1*1301 (HLA-DR13) molecules and compared with published peptide-specific CD4+ T-cell responses. There are more high-affinity ligands (IC50 < 1 micromol/L) derived from the core protein than the surface antigen (P < .04 for HLA-DR1/7/13), but there was no increase in the number or the affinity of ligands for HLA-DR13. Clusters of particular core peptides bound to multiple HLA types, explaining the immunodominance of these regions for T-cell responses. Within the envelope protein, the low-affinity ligands (IC50 < 10 micromol/L) are found mainly in the surface antigen, with a marked paucity of ligands for HLA-DR3 (HLA-DR3 vs. non-DR3; P < .05) consistent with the lower vaccination responses for this HLA type. Of all peptides tested, 8 to 10 bound mainly to one HLA type, allowing a substantially greater breadth of response in heterozygotes. In conclusion, these data offer a mechanistic explanation for the dominant response to the HBV core protein during infection and support the direct involvement of the HLA-DRB1 gene in vaccine nonresponsiveness but not altered susceptibility to viral persistence.